Beginning C# 3.0 - Jack Purdum (Wrox, 2008)
Learn all the basics of C# 3.0 from Beginning C# 3.0: An Introduction to Object Oriented Programming, a book that presents introductory information in an intuitive format. If you have no prior programming experience but want a thorough, easy-to-understand introduction to C# and Object Oriented Programming, this book is an ideal guide. Using the tutorials and hands-on coding examples, you can discover tried and true tricks of the trade, understand design concepts, employ debugging aids, and design and write C# programs that are functional and that embody safe programming practices.